ECAFE AS AN ACTIVE LEARNING TO ENHANCE STUDENTS’ ENGAGEMENT IN LEARNING ENGLISH - Refnita Refnita (English Language Teaching and Research, 2017)
ECAFE (English Communication Activity for Fun and Enjoyable) Learning is a program which was designed to make students actively use English. Through ECAFE Learning, students practiced English through communicative activities. The activities in ECAFE Learning were designed to engage the students to speak in an enjoyable learning process. This program was designed by the West Sumatera Education Department by involving lecturers, teachers and practitioners of education to design the curriculum of ECAFE Learning. Eventhough this program is focus on speaking and listening skills, but reading and writing are also integrated in it. This program was previously proposed to be used for extracurricular activity but later the writer applied it in her regular teaching process in SMAN 3 Padang. The teaching process using ECAFE was designed to suit the curriculum. The teacher had to see the materials and designed the strategies to engage students in learning. There are many techniques that have been applied in ECAFE Learning such as Finding Lost Person, Being an Illustrator, Running Dictation, Strip Line, Selling Product, Mingle, Talk Show and TV program. After implementing ECAFE learning in the classrooms, it showed that the students are active in learning process and engaged in learning English. Moreover, ECAFE also improve students’ ability in speaking as well as increase their self confidence to speak English. Key words: ECAFE, Active Learning, Students’ engagement